Synthesis and assessment of a graphene-based composite photocatalyst - Pedro Magalhães (2015)
A novel composite photocatalyst prepared from graphene and commercial TiO2 (P25 from Evonik) was synthesized, exhibiting enhanced photocatalytic activity for methylene blue degradation, when compared with pristine P25. Additionally, the new catalyst showed 20% more NO conversion under UV light than P25. The band gap of the catalyst, obtained from diffuse reflectance, was 2.95 eV indicating an extended light absorption up to 420 nm. The novel photocatalyst was further tested for inactivating microorganisms showing better results than the reference photocatalyst. Under visible light, the viability loss of the reference bacterial strain Escherichia coil DSM 1103 was two times higher than with the bare P25; it was observed 29% of inactivation with the P25/graphene composite and 14% with the P25 sample, following standard ISO 27447:2009.